2014
DOI: 10.1371/journal.pone.0094238
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Truncated ATHB17 Protein in Maize Increases Ear Weight at Silking

Abstract: ATHB17 (AT2G01430) is an Arabidopsis gene encoding a member of the α-subclass of the homeodomain leucine zipper class II (HD-Zip II) family of transcription factors. The ATHB17 monomer contains four domains common to all class II HD-Zip proteins: a putative repression domain adjacent to a homeodomain, leucine zipper, and carboxy terminal domain. However, it also possesses a unique N-terminus not present in other members of the family. In this study we demonstrate that the unique 73 amino acid N-terminus is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…RNA-seq profiling analysis revealed that ATHB17 acted as a repressor of PhANGs. ATHB17 was reported as a transcriptional repressor containing EAR (ERF-associated amphiphilic repression)-like motif35. Consistent with this result, we found that ATHB17 repressed the transcription of 26 PhANGs under normal or salt stress conditions (Table 2 and Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…RNA-seq profiling analysis revealed that ATHB17 acted as a repressor of PhANGs. ATHB17 was reported as a transcriptional repressor containing EAR (ERF-associated amphiphilic repression)-like motif35. Consistent with this result, we found that ATHB17 repressed the transcription of 26 PhANGs under normal or salt stress conditions (Table 2 and Fig.…”
Section: Discussionsupporting
confidence: 87%
“…We found full length ATHB17 protein had strong self-activation activity. It has been reported that ATHB17 protein lacking the first 113 amino acids (ATHB17Δ113) can still homo-dimerize and specifically recognize the sequence requirements for DNA binding35. Thus we used ATHB17 protein lacking the first 107 amino acids (ATHB17Δ107) for Y1H and electrophoretic mobility shift assay (EMSA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monsanto has developed a biotechnology‐derived inbred line of maize that expresses HB17 (ATHB17), a transcription factor from A. thaliana (Hymus et al ., ; Park et al ., ). Expression of ATHB17 in hybrid maize is associated with increased ear biomass at silking compared to near‐isogenic controls (Rice et al ., ). Increased ear biomass at an early stage of plant development may be indicative of increased sink size and an overall greater grain yield opportunity from hybrid maize at harvest (Borras and Westgate, ; Borras et al ., ; Jones et al ., ; Lee and Tollenaar, ).…”
Section: Resultsmentioning
confidence: 97%
“…There have been copious reports of breakthroughs related to yield improvement and stress tolerance through biotechnology approaches, both in model species (Karaba et al, ; Kirst, Gabilly, Niyogi, Lemaux, & Melis, ; Kromdijk et al, ; Miwa, Takano, & Fujiwara, ; Sade et al, ; Van Camp, ), and in crops (Castiglioni et al, ; Nelson et al, ; Nuccio et al, ; Preuss et al, ; Rice et al, , Nemali et al, ). In many cases, there are reports of yield improvement with limited number of tested environments, and in no known cases, are there reports across multiple germplasm.…”
Section: Discussionmentioning
confidence: 99%